2018
DOI: 10.1071/ah17255
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eHealth on hospital practice: synthesis of the current literature

Abstract: The transition to digital hospitals is fast-moving. Although US hospitals are further ahead than some others in implementing eHealth technologies, their early experiences are not necessarily generalisable to contemporary healthcare because both the systems and technologies have been rapidly evolving. It is important to provide up-to-date assessments of the evidence available. The aim of this paper is to provide an assessment of the current literature on the effects to be expected from hospital implementations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 19 publications
1
41
0
Order By: Relevance
“…Importantly for the purposes of our study, nearly the 50% of both caregivers and clinicians indicated satisfaction levels in the middle range for the item concerning the improvement of patient-clinician communication. This is in line with literature reporting mixed findings on the improvement of communication between patients and clinicians induced by the introduction of technologies into clinical practice [19]. The heterogeneity of findings could be explained, at least in part, by the variety of the aspects related to patient-clinician communication that can be influenced by the use of m-Health, such as the exchange of information, the adequate response to emotion, the management of uncertainty, the decision-making process, and the enhancement of self-management [49].…”
Section: Discussionsupporting
confidence: 91%
“…Importantly for the purposes of our study, nearly the 50% of both caregivers and clinicians indicated satisfaction levels in the middle range for the item concerning the improvement of patient-clinician communication. This is in line with literature reporting mixed findings on the improvement of communication between patients and clinicians induced by the introduction of technologies into clinical practice [19]. The heterogeneity of findings could be explained, at least in part, by the variety of the aspects related to patient-clinician communication that can be influenced by the use of m-Health, such as the exchange of information, the adequate response to emotion, the management of uncertainty, the decision-making process, and the enhancement of self-management [49].…”
Section: Discussionsupporting
confidence: 91%
“…Referring to managerial and policy implications, the paper shows that the use of e-health services depends on enabling technology-supporting relations between patients and well-skilled clinicians. This study fosters observation regarding the need "for hospitals and decision makers to clearly identify and act on the drivers of successful implementations [of e-health solutions]" [74]. Moreover, it reduces uncertainty about the factors having an influence, as many barriers are observed [34].…”
Section: Resultsmentioning
confidence: 62%
“… 8 Findings on the effects of using digital health technology in hospital settings also are not conclusive. 9 In ambulatory and primary care, a recent survey showed an association between the use of electronic medical records and physicians’ burnout and stress, but that other working conditions mattered more. 10 Previous research in Australia found that general practitioners who agreed that IT was useful were more likely to experience higher work–life balance.…”
Section: Introductionmentioning
confidence: 99%